Centro intergeneracional para población infantil de 4 a 6 años y de adultos mayores que residen en el distrito Catedral de San José, Costa Rica - Vargas-Castro, Gloriana (Instituto Tecnológico de Costa Rica., 2019)
This research aims to provide a socio-educational alternative for different ages, in this case, the elderly and children, in order to serve these two sectors in the future. The increase in the population of the elderly, the decrease in the birth rate and the change in the conformation and function of the traditional family exert increasing pressure on the pension and health systems, which leads to seeking care solutions, housing and recreation for an aging society, just as the Government of the Republic has declared (Chinchilla, 2016). The intergenerational centers that support these two groups could, together with other alternatives of the Central Government, become viable solutions where there is an adequate exchange in the rational management of resources and take advantage of what these two groups can generate among themselves, learning from each other and benefiting both with this coexistence. This seeks to achieve not only individual benefits but social benefits. The main goal of the architectural design is to promote the beneficial interrelation between both groups of the population and proposes a viable proposal that considers all the essential elements for its implementation, including: structural, material optimization, space management and circulation flows, security, comfort, application of sustainable strategies, among others.
Proyecto de graduación (Licenciatura en Arquitectura y Urbanismo) Instituto Tecnológico de Costa Rica, Escuela de Arquitectura y Urbanismo, 2012
Keywords: Centros de atención; Adultos mayores; Niños